Pengaruh Work Life Balance, Beban Kerja, dan Kerjasama Tim terhadap Loyalitas Pegawai KPU Kabupaten Ponorogo - Tiwi Rahayu; Umi Farida; Riawan Riawan (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the influence of Work Life Balance, Workload, and Teamwork on Employee Loyalty at the General Election Commission (KPU) of Ponorogo Regency. This research applies a quantitative approach using a saturated sampling technique, in which all 34 employees of KPU Ponorogo Regency were selected as respondents. Data collection was conducted through structured questionnaires distributed to all employees. The collected data were tested using validity and reliability analyses to ensure the accuracy and consistency of the research instruments. Furthermore, multiple linear regression analysis was employed to examine the relationship between independent variables and the dependent variable. The coefficient of determination (R²), t-tests, and F-tests were also performed using SPSS version 29 to determine both partial and simultaneous effects. The findings reveal that Work Life Balance, Workload, and Teamwork each have a positive and significant effect on Employee Loyalty. Simultaneously, these three variables also demonstrate a significant combined influence on Employee Loyalty, indicating that effective balance, manageable workload, and strong collaboration contribute to higher employee loyalty.